Keeping up with the quants : your guide to understanding and using analytics - Davenport, Thomas H., 1954-; Kim, Jinho (Professor of business and statistics) (Boston, Massachusetts : Harvard Business Review Press, 2013)
"In 'Keeping up with the quants', authors, Thomas Davenport and Jinho Kim offer practical tools to improve your understanding of data analytics and enhance your thinking and decision making." -- From the front flap.
Why everyone needs analytical skills -- Framing the problem -- Solving the problem -- Communicating and acting on results -- Quantitative analysis and creativity -- Developing quantitative analysis capabilities -- Working with quants.
Includes bibliographical references and index.
Keywords: Management -- Mathematical models; Decision making -- Mathematical models; Problem solving -- Mathematical models; Decision making -- Mathematical models; Management -- Mathematical models; Problem solving -- Mathematical models